Adaptability of breeds of rams and breed-types of range ewes to market lamb production in Kansas. - Bell, T.D.; Holland, L. (Kansas Agricultural Experiment Station, 2012)
Western ewes of the three predominant types (Texas ewes or fine wools, Blackface crossbreds, and Northwestern Whiteface crossbreds) commonly found in Kansas were secured as ewe lambs in the fall of 1951 and bred to Hampshire, Suffolk, Shropshire, and Southdown rams two seasons. A different set of yearling rams has been used each year and the ewes are being rotated so that the same ewes are not bred to the same breed of ram each year. Lamb production and wool production records are being obtained from the different types of ewes and lamb production figures are being obtained for the four sire groups.
Keywords: Sheep; Rams; Range ewes; Production; Wool-types